Editorial. Climate, Society and Environment - Serrano Notivoli, Roberto; Saz, Miguel Ángel; Tejedor, Ernesto (Geographicalia, 2021)
The journal GEOGRAPHICALIA has been uninterruptedly published since 1977, being one of the oldest Geography active journals in Spain. In these more than 40 years, the study that Geography makes of the three disciplines addressed by this number, "Climate, Society and Environment", has been highly transformed, both in the approaches and tools, as well as in the contents and interests. GEOGRAPHICALIA has witnessed this evolution providing, to a greater or lesser extent, its part to the knowledge of all of them, especially in Spain and Latin America. Professor J.M. Cuadrat, pioneer of climatic research in the Department of Geography and Regional Planning from the University of Zaragoza, has accompanied this journal during all its trajectory, notably contributing with many colleagues.